Price Measurement and Mismeasurement in Central Asia - Koen, Vincent (IMF Working Papers; Working Paper ;, 1995)
The vertiginous increases in the overall price level and dramatic swings in relative prices experienced by Kazakhstan, the Kyrgyz Republic, Tajikistan, Turkmenistan, and Uzbekistan since the onset of the transition rendered their traditional Paasche retail price indices obsolete and called for the introduction of Laspeyres consumer price indices. While the latter represent a major improvement, several measurement or interpretation issues remain, reflecting various potential index number biases, dispersion of prices and inflation across geographical areas and social groups, discontinuities in the inflation process, residual shortages, and seasonality.